2020
DOI: 10.1038/s41598-020-71922-x
|View full text |Cite
|
Sign up to set email alerts
|

Infant gut microbiota characteristics generally do not modify effects of lipid-based nutrient supplementation on growth or inflammation: secondary analysis of a randomized controlled trial in Malawi

Abstract: An unhealthy gut microbial community may act as a barrier to improvement in growth and health outcomes in response to nutritional interventions. The objective of this analysis was to determine whether the infant microbiota modified the effects of a randomized controlled trial of lipid-based nutrient supplements (LNS) in Malawi on growth and inflammation at 12 and 18 months, respectively. We characterized baseline microbiota composition of fecal samples at 6 months of age (n = 506, prior to infant supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 79 publications
2
11
1
Order By: Relevance
“…These data suggest that this programmed microbial maturation is driven strongly by age, and is robust to changes in WASH and complementary feeding, as delivered in this trial, and that potential microbiome-mediated pathways affecting early-life growth occur independently of these specific interventions. Improvements in growth as a result of the IYCF intervention are not driven by the microbiome, as supported by previous reports showing that the gut microbiome does not mediate the effect of lipid-based IYCF nutrient supplements on child growth 44 . More intensive interventions that target WASH, microbial exposures, nutrient intake and microbiota-directed foods during the first 2 years of life may be required to modify this programmed trajectory of gut microbiome succession.…”
Section: Discussionsupporting
confidence: 74%
“…These data suggest that this programmed microbial maturation is driven strongly by age, and is robust to changes in WASH and complementary feeding, as delivered in this trial, and that potential microbiome-mediated pathways affecting early-life growth occur independently of these specific interventions. Improvements in growth as a result of the IYCF intervention are not driven by the microbiome, as supported by previous reports showing that the gut microbiome does not mediate the effect of lipid-based IYCF nutrient supplements on child growth 44 . More intensive interventions that target WASH, microbial exposures, nutrient intake and microbiota-directed foods during the first 2 years of life may be required to modify this programmed trajectory of gut microbiome succession.…”
Section: Discussionsupporting
confidence: 74%
“…Our results are in contrast to a previous RCT that investigated infant microbiome composition as a modifier of SQ-LNS impact on infant growth In Malawi 48 . However, in the primary analyses of that RCT, there was no effect of SQ-LNS on linear infant growth 94 .…”
Section: Discussioncontrasting
confidence: 99%
“…Gut microbiota composition, therefore, may also be an important modifier of dietary interventions on infant health. Only one study to date investigated the gut microbiota as an effect modifier of SQ-LNS on infant stunting, and reported limited evidence of effect-modification 48 . However, several studies have reported a synergistic effect of microbiome composition and diet on undernutrition phenotypes using animal models 26,27,49,50 .…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that this programmed microbial maturation is robust to changes in WASH and complementary feeding, as delivered in this trial, and that potential microbiome-mediated pathways affecting early-life growth occur independently of these specific interventions. Improvements in growth as a result of the IYCF intervention are not driven by the microbiome, as supported by previous reports showing that the gut microbiome does not mediate the effect of lipid-based IYCF nutrient supplements on child growth (39). More intensive interventions that target WASH, microbial exposures, nutrient intake and microbiota-directed foods during the first 2 years of life may be required to modify this programmed trajectory of gut microbiome succession.…”
Section: Discussionsupporting
confidence: 69%